Emotionally intelligent school counseling - Pellitteri, John.; Shelton, Claudia; Stern, Robin; Muller-Ackerman, Barbara (Mahwah, N.J. : L. Erlbaum Associates, 2006)
The concept of emotional intelligence (EI), which has steadily gained acceptance in psychology, seems particularly well suited to the work of school counselors and school psychologists who must constantly deal with troubled and underperforming students. [This] book ... systematically explaine[s] the theoretical and scientific foundations of emotional intelligence and integrate[s] this information into the roles and functions of school counselors and other school personnel. In addition to illustrating how social emotional learning is important to both individual students and to school climate, the book also shows school counselors how to expand their own emotional awareness and resiliency. Key features of this ... book include: ASCA Guidelines -- the book integrates the latest findings from the field of social emotional learning with the new ASCA guidelines for school counselors; Real-life Cases -- the book moves quickly from an overview of basic definitions, theories, and guidelines to stories of real counselors, administrators, teachers, and parents.-Back cover.
Includes bibliographical references and indexes.
Keywords: Educational counseling; Emotional intelligence; EDUCATION -- Counseling -- -Vocational Guidance